Sustainability Potential of Kikuyu Grass (Pennisetum clandestinum) in Livestock Farming of Peru's Highland Regions - Alvarez García, Wuesley Yusmein; Díaz, Arturo; Becerra, Yessica; Vallejos Fernández, Luis A.; Florián Lescano, Roy Roger; Carrasco Chilón, William Leoncio; Cervantes Peralta, Marieta Eliana; Quilcate Pairazaman, Carlos; Muñoz Vilchez, Yudith (MDPI, 2025)
The productive sustainability of Pennisetum clandestinum in the Peruvian highlands was evaluated through productivity, growth and chemical composition. The effect of the nitrogen (N) rate, organic matter application, and cutting frequency on Kikuyu grass's yield, chemical composition, plant height, and growth rate was investigated. Experimentation followed a randomized block design with split plots. Multivariate analysis of variance (MANOVA) assessed differences across study factors. Applying 120 kg of N ha-1 yr-1 raised the protein yield to 3454.53 kg ha¯¹, with a crude protein (CP) content of 23.54%. Moreover, cypress (Cupressus lusitanica) trees influenced the Kikuyu biomass, producing 19,176.23 kg of dry matter (DM) ha-1 yr-1 at 8.5-11.5 m from the tree base. Organic matter enhanced Kikuyu aboveground biomass. While dry matter production showed no significant difference between 30- and 60-day cutting intervals, CP content was higher at 30 (p < 0.05). Peak daily dry matter (DM) production occurred at 45 days, achieving a biomass accumulation of 21,186.9 kg DM ha-1 yr-1. Given its high yield and favorable chemical composition, Kikuyu is a viable option for dairy cattle feed, especially in highland areas. Implementing a plant improvement program for Kikuyu could further enhance its nutritional value for high-production dairy cows.